The Kingfisher book of the ancient world / from the ice age to the fall of Rome - Martell, Hazel (New York : Kingfisher, 2001)
Richly illustrated with maps and reconstruction of everyday life, this resource book explores the geography, culture and history of the ancient world. Full-color illustrations.
Includes index.
Keywords: Civilization, Ancient -- Juvenile literature; Civilization, Ancient